Analysis of multifunctional graphene-based hyperbolic metamaterials at mid-infrared frequencies - Oishi Jyoti; Md. Samiul Habib; Nguyen Hoang Hai; S.M. Abdur Razzak (Results in Optics)
We conceptualize and theoretically explore a compact, tunable, and multifunctional device using graphene-based hyperbolic metamaterials (HMMs). We model our device using an effective medium theory and apply a standard transfer matrix approach to calculate the reflectance spectrum at mid-infrared frequencies. Our theoretical analysis suggests that by carefully tailoring the properties of graphene, the dispersion profile of the HMM is switchable between ellipse and hyperbola, where two types (Type-I and Type-II) of hyperbolic dispersion profile can be obtained simultaneously: Type-I HMM is located in the wavelength range of 1.4μm to 1.6μm whilst Type-II HMM ranges from 3.3μm to 8μm. We show that by changing the chemical potential (μc) of the graphene, the reflectance spectra of the device can be shifted to the shorter wavelengths. Our analysis also demonstrates that for a fixed μc, the reflectance spectra of the device can be further blue-shifted by increasing the number of graphene monolayers. Notably, we find that the reflectance spectra remain largely unaffected by the transverse polarization (TE/TM modes) of the incoming waves. We also test the transmission properties of two sub-wavelength slits through a straight section of the graphene-based metamaterial slab at 1.5μm, observing that our device is capable of resolving the deep sub-wavelength features at the output end of the slab. At 1.5μm, we also examine the propagation of light through a graphene-based magnifying hyperlens, achieving a three-fold image magnification at the output surface. Finally, we compare the calculated intensity profile for two-slits with the numerical simulation, finding good agreement between them. We believe that our proposed metamaterial-based multifunctional device would be a suitable candidate for creating imaging devices and tunable filters.